Corticosterone and decision-making in male Wistar rats: the effect of corticosterone application in the infralimbic and orbitofrontal cortex - Koot, Susanne; Koukou, Magdalini; Baars, Annemarie; Hesseling, Peter; van ’t Klooster, José; Joëls, Marian; van den Bos, Ruud (Frontiers in Behavioral Neuroscience, 2014)
Corticosteroid hormones, released after stress, are known to influence neuronal activity and produce a wide range of effects upon the brain. They affect cognitive tasks including decision-making. Recently it was shown that systemic injections of corticosterone disrupt reward-based decision-making in rats when tested in a rat model of the Iowa Gambling Task (rIGT), i.e. rats do not learn across trial blocks to avoid the long-term disadvantageous option. This effect was associated with a change in neuronal activity in prefrontal brain areas, i.e. the infralimbic (IL), lateral orbitofrontal (lOFC) and insular cortex, as assessed by changes in c-Fos expression. Here, we studied whether injections of corticosterone directly into the IL and lOFC lead to similar changes in decision-making. As in our earlier study, corticosterone was injected during the final 3 days of the behavioural paradigm, 25 minutes prior to behavioural testing. Infusions of vehicle into the IL led to a decreased number of visits to the disadvantageous arm across trial blocks, while infusion with corticosterone did not. Infusions into the lOFC did not lead to differences in the number of visits to the disadvantageous arm between vehicle treated and corticosterone treated rats. However, compared to vehicle treated rats of the IL group, performance of vehicle treated rats of the lOFC group was impaired, possibly due to cannulation/infusion-related damage of the lOFC affecting decision-making. Overall, these results show that infusions with corticosterone into the IL are sufficient to disrupt decision-making performance, pointing to a critical role of the IL in corticosteroid effects on reward-based decision-making. The data do not directly support that the same holds true for infusions into the lOFC.